Representasi Keterkaitan Lagu Anak Jaman Dahulu dengan Kehidupan Jaman Sekarang - Umi Novitasari; Nadia Amalia (UIN Raden Mas Said Surakarta, 2018)
This study aims to determine the representation of children's songs of the era of 90'an and how its relevance to children today. Seeing the phenomenon of songs that do not educate for children today is far from civilization in the past. They began to leave the 90s era song and move on to adult songs that already have different content. The research method used is descriptive qualitative with semiotic analysis of S. Pierce. The object of research is the 90s era child's song. The research procedure begins with collecting the 90s era song and analyzing the song. The results of the study show that the representation of the 90s era children's songs such as the life cycle from the waking up, going to school, helping the parents in the fields or gardening, playing with friends. The relevance of the 90s era song with today is different. Children today are rarely found willing to shepherd and gardening they are busy school and busy with themselves even some who do not want to help his parents. In another song the old boy happily play with friends their age, inversely proportional to the present day fellow play is an adult and more fun with their gadgets by playing games or watching videos.